Non-invasive biomarkers of eosinophilic esophagitis - Votto, Martina; De Filippo, Maria; Castagnoli, Riccardo; Delle Cave, Francesco; Giffoni, Francesca; Santi, Viola; Vergani, Marta; Caffarelli, Carlo; De Amici, Mara; Marseglia, Gian Luigi; Licari, Amelia (Acta Biomedica Atenei Parmensis, 2021)
Eosinophilic esophagitis (EoE) is an emerging allergen-mediated disease characterized by symptoms of esophageal dysfunction and eosinophilic inflammation. EoE diagnosis requires 15 eosinophils per high power field (eos/HPF) in tissue biopsies endoscopically obtained. The need for several endoscopies to monitoring the disease and the absence of validated non-invasive biomarkers or tools are the main reasons for the significant burden on affected patients and the healthcare system. There is a critical need for non-invasive or minimally invasive biomarkers. In the last years, several efforts have been made to identify potential biomarkers for diagnosing and monitoring the disease that we summarized in this review. The future of EoE is exciting from both a diagnostic and therapeutic standpoint. Further research is required to confirm phenotypes and histological or serological biomarkers to provide a novel endotype classification based on different cytokine or genetic signatures relevant to precision medicine.